IMPLEMENTASI PROGRAM PENTA HELIX DALAM PROGRAM MEDIA DAN PUBLIKASI DESA - Nani Harlinda Nurdin; Faizah Mahi; Dian Mirnawaty Sultan; Zulkarnain Hamson (Indonesian Collaboration Journal of Community Services (ICJCS), 2023)
Alumni Family Association (IKA) of the Faculty of Social and Political Sciences (FISIP) Hasanuddin University (UNHAS) involving members from representatives of State (PTN) and Private Universities (PTS), and the Regional Management Council (DPD) of Indonesian Online Journalists (JOIN) Bone Regency, South Sulawesi (Sulsel), led by Zulkarnain Hamson, Chair of the Community Service Team (PKM), with three facilitator lecturers, carried out Village Journalism training with the theme: "Building an Information System that supports the Publication of Village Potential" as part of the model implementation Pentahelix. Of the 27 sub-districts in Bone Regency, Palakka is the pilot project for organizing Village Journalism and is the first to be implemented in Bone. Head of District Area, Andi Akbar Baso SH. appreciated the Village Journalism training, when welcoming the JOIN team of lecturers and administrators, in order to improve the human resources of 15 villages in the region. Each village sends 2 staff, to take place in the sub-district office hall for one day. The training was considered successful in achieving targets, with participants increasing their understanding of the importance of using media for village publications